Pengaruh Model Pembelajaran Project Based Learning Terhadap Kemandirian Dan Kreativitas Siswa Pada Materi Akutansi Keuangan di SMKN 1 Kamal - Musdalifah, Nurul; Kusmiati; Muhajir (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2024)
In this research, to determine the interaction of the PjBL learning model on student independence and creativity in financial accounting material at SMKN 1 Kamal. In this study, the samples were 2 classes with 25 students each. By referring to the problem that has been explained in the background of the problem, the researcher took the initiative to conduct research with the title The influence of the project-based learning model on student independence and creativity in financial accounting material at SMKN 1 Kamal. From the results obtained using the MANOVA test or Multivariate Analysis of Variance, namely with a significance level of 0.000 < 0.05. So, there is a difference between those who use Pjbl on the independence and creativity of SMKN 1 Kamal students. So the PjBL learning model has a significant effect on student creativity in financial accounting material at SMKN 1 Kamal